2020
DOI: 10.1177/1756284820961299
|View full text |Cite
|
Sign up to set email alerts
|

Berberine for diarrhea in children and adults: a systematic review and meta-analysis

Abstract: Background: Diarrhea is a ubiquitous digestive system disease, leading to loss of fluid and electrolytes, and may be life-threatening, especially in children and adults who are immunosuppressed or malnourished. Berberine has a broad-spectrum antibiotic activity and is very widely used to treat diarrhea in China. No systematic review has been carried out to evaluate the evidence presented in clinical trials. The aim of this study was to assess the effectiveness and safety of berberine in diarrhea treatment amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…The latter may even be improved due to the higher lipophilicity and thus more balanced bioavailability of the ligands [65]. Accordingly, the activity of these derivatives in the treatment of tuberculosis [7], diarrhea [8], diabetes [9], cardiovascular diseases [10] or high cholesterol levels [11] is worth to be tested, because the parent berberine is already employed as drug for these diseases. In summary, a new complementary class of arylated berberine derivatives was discovered, which may constitute a promising starting point for the development of lead structures in drug discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter may even be improved due to the higher lipophilicity and thus more balanced bioavailability of the ligands [65]. Accordingly, the activity of these derivatives in the treatment of tuberculosis [7], diarrhea [8], diabetes [9], cardiovascular diseases [10] or high cholesterol levels [11] is worth to be tested, because the parent berberine is already employed as drug for these diseases. In summary, a new complementary class of arylated berberine derivatives was discovered, which may constitute a promising starting point for the development of lead structures in drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the latter is established in traditional Chinese medicine as source for anti-inflammatory extracts [2]. Berberine has also been employed in modern medicine because of its antimicrobial [3], antiprotozoal [4], antiviral [5], and anti-inflammatory [6] activity, and it is used in the treatment of tuberculosis [7], diarrhea [8], diabetes [9], cardiovascular diseases [10] or high cholesterol levels [11]. Most interestingly, it has been found that berberine (1a) exhibits a selective cytotoxicity against cancer cells [12,13], which is mainly based on its DNAbinding properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…of various diseases [35][36][37][38]. Moreover, these compounds exhibit a light-up effect upo binding to polyanionic analytes like DNA, which is, however, rather unselective for th parent berberine [28,33,39,40].…”
Section: Synthesismentioning
confidence: 99%
“…In fact, many fluorescent light-up probes based on these natural products have been developed that show a highly selective increase in their emission intensity upon binding to G4-DNA [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Among the natural products, berberine and its derivatives are extensively studied substrates because the biocompatibility of this class of compounds has been demonstrated with their application in the treatment of various diseases [ 35 , 36 , 37 , 38 ]. Moreover, these compounds exhibit a light-up effect upon binding to polyanionic analytes like DNA, which is, however, rather unselective for the parent berberine [ 28 , 33 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Berberine (BBR, Figure 1), a Chinese natural product extracted from Coptis chinensis, has been widely used as an over-the-counter (OTC) drug to treat bacterial-caused diarrhea in China for decades. 1 Over the past 20 years, its multiple pharmacological activities have been discovered and elucidated, including antiinflammatory, antitumor, hypoglycemic, hypolipidemic, antivirus, etc, [2][3][4][5][6][7][8][9][10][11] suggesting a typical multitargetdirected mechanism of BBR. A couple of classical cellular pathways, such as NIMA-related kinase 7 (NEK7)/nucleotide-binding domain-like receptor protein 3 (NLRP3) and c-Jun N-terminal protein kinases (JNK)/stress activated protein kinases (SAPKs), as well as interleukin-6 (IL-6)/signal transducer and activator of transcription 3 (STATs), 8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] have been proven to closely account for BBR's polypharmacological effects.…”
Section: Introductionmentioning
confidence: 99%